2010
DOI: 10.1162/pres.19.3.230
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Viewing a Self-Avatar on Distance Judgments in an HMD-Based Virtual Environment

Abstract: Few HMD-based virtual environment systems display a rendering of the user’s own body. Subjectively, this often leads to a sense of disembodiment in the virtual world. We explore the effect of being able to see one’s own body in such systems on an objective measure of the accuracy of one form of space perception. Using an action-based response measure, we found that participants who explored near space while seeing fully-articulated and tracked visual representation of themselves subsequently made more accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(136 citation statements)
references
References 43 publications
5
125
2
Order By: Relevance
“…It should be mentioned though that even calibrated HMDs are not free of geometric distortions (Kuhl et al 2009) which could have some influence on the estimation of the relative position of the virtual with respect to the real hand. However, it has also been found that such egocentric distance judgments improve when the participant is represented by an avatar (Mohler et al 2010). …”
Section: Proprioceptive Driftmentioning
confidence: 99%
“…It should be mentioned though that even calibrated HMDs are not free of geometric distortions (Kuhl et al 2009) which could have some influence on the estimation of the relative position of the virtual with respect to the real hand. However, it has also been found that such egocentric distance judgments improve when the participant is represented by an avatar (Mohler et al 2010). …”
Section: Proprioceptive Driftmentioning
confidence: 99%
“…Recent studies have shown that presenting a self-avatar, which is a virtual body animated by subject, in a virtual environment can improve the accuracy of subject's egocentric distance estimation [Mohler, Creem-Regehr, Thompson, & Bülthoff, 2010;. Although some work has not found such effects [Geuss, Stefanucci, Creem-Regehr, & Thompson, 2010;McManus et al, 2011], we can infer that self-avatars can provide a more realistic way for people to interact with virtual environments.…”
Section: Introductionmentioning
confidence: 89%
“…Mohler et al (2010) stresses the importance of body representation in VR environments and shows that it significantly improves the users' ability to accurately judge scale and distance. Kulik et al (2011) focus on the importance of multi-user support in VR, and even state that it isn't VR if it isn't multi-user.…”
Section: Vr Technologies Related To Adaptation Of Manufacturing Procementioning
confidence: 98%
“…There are ways of recording and rendering the users body and posture back into the virtual environment in real time, examples of this is using VR-gloves or 3D imaging sensors to map the user's movements (Korves and Loftus 2000;Mohler et al 2010). If such a mapping is performed, this solution can support multi-user environments through rendering the mapped body and postures or an avatar representation of them back into the virtual environment (Beck et al 2013;Mohler et al 2010). Recent technological development has significantly decreased the cost of HMDs, compared to when the cited work was written.…”
Section: Vr Technologies Related To Adaptation Of Manufacturing Procementioning
confidence: 99%